Microbiome and Antimicrobial Resistance in Members of the Enterobacteriaceae Family from Vaginal and Preputial Mucous Isolates of Stray Dogs - Rey, Laisa Marina Rosa; Guaitolini, Carlos Renato de Freitas; Fazoli, Kawany Gabrieli Zanetti; Silva, Lucas Lima da; Fendrigo, Túlio Tozzi; Santos, Isabela Carvalho dos; Zaniolo, Melissa Marchi; Martins, Lisiane de Almeida; Gonçalves, Daniela Dib (Acta Scientiae Veterinariae, 2020)
Background: Contact between humans and pets, mainly dogs and cats, has been increasing in recent years, which may result in the spread of infectious agents to new hosts and even to the environment, causing emergencies of national and international interest. The aim of this work was to understand the phenotypic profile of bacteria of the Enterobacteriaceae family of vaginal and preputial mucous of stray dogs from a border region. Materials, Methods & Results: Swab samples from the vaginal and preputial mucosa of stray dogs from two border regions were collected for later bacterial isolation, biochemical identification of bacterial isolates, susceptibility tests to different antimicrobials, and determination of the bacterial resistance index. Samples were collected from 70 animals, was possible to isolate 88 samples, of which 36 (40.9%) presented isolates of Gram-negative bacteria, with Escherichia coli being the most prevalent species (44.8%), followed by Obesumbacterium proteus in eight (27.5%); Enterobacter aerogenes and Enterobacter cloacae in two (6.8%); and Erwinia herbicola, Koserella trabulsii, Proteus mirabilis, and Serratia rubidaea (3.4%) from one isolate. The most resistant antimicrobials Clindamycin (100%), Metronidazole (100%), Oxacillin (100%), and Penicillin (100%) were tested against the vaginal and preputial samples and when the multidrug resistance index of the isolates was analyzed, all were classified as presenting a public health risk. Discussion: The results of this work suggest that stray dogs may be considered potential reservoirs of resistant pathogenic microorganisms, enabling future health problems due to the close coexistence of tutors with their dogs. It is known that the microorganisms that inhabit a certain environment or a specific part of the body are collectively called microbiomes. More specifically, some of them are bacteria that inhabit the reproductive mucous membranes (vaginal and preputial) of healthy dogs. Several works have also identified E. coli as the most prevalent bacteria identified in the vaginal and preputial mucosa of healthy dogs, that is regarded as a member of different microbiomes that is a commensal of different species of domestic animals, it is important to stress that this bacterial species presents sophisticated virulence mechanisms possibly responsible for different nosocomial infections as well as community infections in mankind and different species of animals. Found other bacterial species suggests a connection of these bacterial species with different environments and different animal species, which is even more disturbing regarding public health, since most of the time dogs share the same spaces of their tutors, which would facilitate the transmission and interaction with potentially pathogenic microorganisms. The MAR index result is worrying when dealing with stray and asymptomatic dogs, since the behavioral particularities of canine species such as licking the body, licking the genitalia, sniffing the environment for territorial demarcation and, in some cases, coprophagy, may facilitate the transmission of pathogenic microorganisms and even disseminate genes of resistance to their keepers, other animals, and even to the environment. Unique health education works should be conducted in border regions in order to raise awareness of the population involved about the different situations that may favor the dissemination of microorganisms and their resistance genes, including the problems caused by the illegal sale and/or transportation of drugs, a situation that is very common in borders.